Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1161/circulationaha.106.680827
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Power Loss During Exercise in Single-Ventricle Patients After the Fontan

Abstract: Background-We previously demonstrated that power loss (PL) through the total cavopulmonary connection (TCPC) in single-ventricle patients undergoing Fontan can be calculated by computational fluid dynamic analysis using 3-dimensional MRI anatomic reconstructions. PL through the TCPC may play a role in single-ventricle physiology and is a function of cardiac output. We hypothesized that PL through the TCPC increases significantly under exercise flow conditions. Methods and Results-MRI data of 10 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
191
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(201 citation statements)
references
References 27 publications
6
191
3
Order By: Relevance
“…The patientspecific TCPC CFD analysis methodology and in vitro validations of these techniques have been described in previous studies (27,29,42). For each patient geometry, blood flow was modeled at baseline steady-state flow conditions by setting SVC and IVC flows to values derived from PC MRI averaged over the cardiac cycle.…”
Section: ϫ2mentioning
confidence: 99%
See 2 more Smart Citations
“…The patientspecific TCPC CFD analysis methodology and in vitro validations of these techniques have been described in previous studies (27,29,42). For each patient geometry, blood flow was modeled at baseline steady-state flow conditions by setting SVC and IVC flows to values derived from PC MRI averaged over the cardiac cycle.…”
Section: ϫ2mentioning
confidence: 99%
“…A study by Szabo et al (40) reported increased E a and decreased E es as well using pressure-volume analysis conducted on measurements made in a dog SV model. In addition to experimental studies, theoretical models have also predicted similar changes in E a , E es , and cardiac reserve in a Fontan circulation (14,22,28).Most of the studies thus far on the Fontan circulation can be broadly categorized into two types: 1) those that study the Fontan circulation as a whole using in vivo animal and human studies (35,36,40); and 2) those that study the fluid mechanics of the surgically created TCPC in isolation from the SV circulation (27,41,42). There have not been many studies that have connected the two, i.e., those that relate the hemodynamics of the TCPC to upstream hemodynamics and cardiac function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the effects of exercise on caval vein and pulmonary artery flow after Fontan operation have emphasized the need for evaluation of the Fontan circulation under exercise conditions (15,16). In Fontan patients, PA flow has been studied directly after supine bicycle exercise with magnetic resonance imaging (MRI) (16).…”
mentioning
confidence: 99%
“…Recent attempts to quantify the pulsatility in Fontan patients revealed significant differences among different patient cohorts and suggested pulsatility as a promising parameter to predict late Fontan failure (10). Due to the absence of right heart active pumping source, minimized energy loss inside the total cavopulmonary connection (TCPC) pathway has been suggested for the best optimal surgical outcomes (11)(12)(13)(14). In our study, as the phase I step, we investigated the caval flow dynamics and the associated changes in pathway power loss for failing Fontan patients.…”
Section: Introductionmentioning
confidence: 99%